Empowerment for Whom? Empowerment for What? Lessons from a Participatory Action Research Project - Meagan Call-Cummings; Christine James (Networks: An Online Journal for Teacher Research, 2015)
This article sets forth the process through which I, an educator of over 20 years, my research mentor, and my 52 Latino/a students answered questions that were important to us through participatory action research. I start the process by asking if and how I am empowering my students, and they start their own parallel process by asking about their relationships with their White teachers. By engaging in various data collection approaches, including Boal’s (1985) Theatre of the Oppressed and Photovoice, we are all able to answer these questions. I learn that as a teacher I do not empower students; they empower themselves. As we conduct the research together I watch them and see the processes of empowerment the students go through for myself. I learn how as an educator I can create empowering situations and opportunities my students can take advantage of in the future. In parallel experiences, the students learn that they have always had a voice, but this project helps them discover – and use – the voices they have always had. Overall, our group finds that empowerment takes place in spaces and moments of mutual, active inquiry, where individual voices can be raised to re-imagine what can and should be taking place within our schools.